Коллектор электрической машины - Бекишев Р. Ф. Рудольф Фридрихович; Данекер В. А. Валерий Аркадьевич; Качин С. И. Сергей Ильич; Константинов Г. Г. Геннадий Григорьевич; Чиндяскин В. И. Владимир Иванович
опубл. 15.09.85